Magneto-plasticity in micro-cutting of single-crystal copper. (10th October 2022) - Guo, Yunfa; Lee, Yan Jin; Zhang, Yu; Wang, Hao
Highlights: Magneto-plasticity can be induced by a weak magnetic field in micro-cutting. Cutting force, chip and machined surface are affected by magneto-plasticity. Magneto-plasticity shows anisotropy with magnetic field direction. Directional dislocation flow results in anisotropic magneto-plasticity. Abstract: The plasticity of metals can be significantly affected by the application of a magnetic field, otherwise known as the magneto-plastic effect. This paper investigates the magneto-plastic effect in the micro-cutting of a non-magnetic ductile material, single-crystal copper, under a weak magnetic field and reports the influence of the phenomenon on the cutting forces and machined surface quality. A softening effect was observed from the large reduction in cutting forces from 3.2 N to 1.5 N under the magnetic field. As compared to the magnetic field intensity and polarity, the variation in magnetic field orientations with respect to the cutting direction exhibited a stronger influence on the cutting force, chip morphology, machined surface texture, subsurface microstructure, surface roughness, and machined surface microhardness of the copper sample. An analytical model was developed based on the geometry of the cutting chips to correlate the orientation-dependent influence of the magnetic field on the cutting forces. On the surface quality, excessive folds with four different types of morphology produced under magnetic-free cutting were suppressed after applying the magnetic field with the most significant improvement achieved with the 90° magnetic field direction. The magnetic-assisted changes in machined surface morphology also led to the reduction in machined surface roughness and microhardness. The optimistic micro-cutting outcomes in this work establish a greater understanding of the magneto-plastic effect and demonstrate the applicability of magneto-plasticity in ultraprecision manufacturing.